Caravaggio - Angelo Longoni (2007)
The tumultuous and adventurous life of Michelangelo Merisi, controversial artist, called by Fate to become the immortal Caravaggio. A violent genius that will dare to defy the ideal vision of the world imposed by the Renaissance painters. A provoker that scandalized patrons and institutions, raising the altars the outcast figures he knew so well: drunkards, vagrants and prostitutes.
Keywords: Biography, History